2016
DOI: 10.1016/j.poly.2016.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and crystal structures of molybdenum complexes of unsymmetrical electron-poor dithiolene ligands

Abstract: Mo(S 2 C 2 (CF 3) 2) 3 , 1a, has proven a useful p-dopant in organic electronics. To develop more soluble p-dopants, MoS 9 2was treated with alkynes CF 3 CCCO 2 Me and CF 3 CCCOCF 3 to give the dianions of the corresponding tris(dithiolene) complexes, 1b 2and 1c 2-, respectively, which were then oxidized to neutral molybdenum tris[1-(methoxycarbonyl)-2-(trifluoromethyl)-ethane-1,2-dithiolene], 1b, and molybdenum tris[1-(trifluoroethanoyl)-2-(trifluoromethyl)ethane-1,2-dithiolene], 1c, using NO + PF 6-. The cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 72 publications
2
44
0
Order By: Relevance
“…Although the air-stability of these molecular dopants is well-known, [34][35]43 our findings demonstrate the reliability of optoelectronic devices that employ these dopants. In summary, we have demonstrated that charge-carrier extraction in the latest brand of high performing, single-step deposited PbS CQD based solar cells is limited by the moderate p-type character of the EDT-PbS CQD HTL, which allows only limited band bending under maximum power point operation.…”
Section: Toc Graphicsmentioning
confidence: 70%
“…Although the air-stability of these molecular dopants is well-known, [34][35]43 our findings demonstrate the reliability of optoelectronic devices that employ these dopants. In summary, we have demonstrated that charge-carrier extraction in the latest brand of high performing, single-step deposited PbS CQD based solar cells is limited by the moderate p-type character of the EDT-PbS CQD HTL, which allows only limited band bending under maximum power point operation.…”
Section: Toc Graphicsmentioning
confidence: 70%
“…Furthermore, neither neutral Mo(tfd-COCF 3 ) 3 nor its anion absorbs at 800 nm. 27 A combination of spectroelectrochemistry and chronoamperometry allowed us to determine the molar attenuation coefficient ε P2 of the first sub-bandgap polaron peak P2. Our electrochemical setup consisted of a spin-coated P3HT film on the indium tin oxide (ITO) working electrode, a platinum wire counter electrode, and a silver wire as pseudo reference electrode, immersed in an electrolyte solution of 0.1 M tetrabutylammonium hexafluorophosphate (TBAPF 6 ) in AcN (see the Experimental Section for details).…”
Section: Resultsmentioning
confidence: 99%
“…During electrochemical oxidation PF 6 – counterions, which have a thermochemical radius of r = 2.4 Å, 30 enter the polymer from the electrolyte. Chemical doping instead produces Mo(tfd-COCF 3 ) 3 – counterions, which have a much larger radius of r ∼7.5 Å (based on an estimate of the smallest sphere that could encompass the molecule/ion), 27 and hence results in a larger average polaron–anion distance. 31 Because the P2 polaron absorbance is broad, we deem the difference in peak position to be minor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Redox potentials of the molybdenum complexes were determined by differential pulse voltammetry in dichloromethane / 0.1 M Bu4NPF6 using a BAS potentiostat, a glassy carbon working electrode, a platinum auxillary electrode, a AgCl-coated Ag wire as a pseudo-reference electrode, and ferrocene or cobaltocenium hexafluorophosphate to internally reference the voltammograms to the ferrocenium/ferrocene couple (E(CoCp2 +/0 ) = -1.32 V vs. FeCp2 +/0 ). [81] The redox potential for Magic Blue was taken from ref [48]. The effective redox potentials for the organometallic dimers were estimated from Eq.…”
Section: Methodsmentioning
confidence: 99%